Mining the Proteome of Streptococcus mutans for Putative Drug Targets - Marimuthu, Shakti C. V.; Ravinarayanan, Haribalaganesh; Rosy, Joseph C.; Sundar, Krishnan (Infectious Disorders - Drug Targets, 2021)
Background: Dental caries is the most common and one of the prevalent diseases in the world. Streptococcus mutans is one of the major oral pathogens that cause dental caries by forming a biofilm on dental tissues, degrading dental enamel and consequent cavitation in the tissue. In vitro selection of drug targets is a laborious and expensive process and therefore, computational methods are preferable for target identification at the initial stage. Objective: The present research aims to find new drug targets in S. mutans by using subtractive proteomics analysis, which implements various bioinformatics tools and databases. Methods: The proteome of S. mutans UA159 was mined for novel drug targets using computational tools and databases such as: CD-HIT, BLASTP, DEG, KAAS and CELL2GO. Results: Out of 1953 proteins of S. mutans UA159, proteins that are redundant, homologous to human and non-essential to the pathogen were eliminated. Around 178 proteins already available in drug target repositories were also eliminated. Possible functions and subcellular localization of 32 uncharacterized proteins were predicted. Substantially, 13 proteins were identified as novel drug targets in S. mutans UA159 that can be targeted by various drugs against dental caries. Conclusion: This study will effectuate the development of novel therapeutic agents against dental caries and other Streptococcal infections.
Keywords: subtractive proteomics